Mystical love metaphors: a cognitive analysis of Sohrab Sepehri’s poetry - Sareh Jaberi,; Imran-Ho-Abdullah,; Ravichandran Vengadasamy, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Metaphor in poetic texts has been discussed from different perspectives. Philosophers and rhetoricians conceive of metaphor as an instrument utilized in the composition of literary texts, though metaphor proper was construed as ornamentation within a text. In cognitive linguistics, metaphor is not only confined to literary studies but it has become a commonality among all the sciences that address issues related to language and mind and it demonstrates the various ways we perceive our experiences. The present study is an investigation of mystical love metaphors in Sohrab Sepehri’s poetry by drawing upon conceptual metaphor theory (CMT). Studying mystical metaphors via conceptual metaphor theory will provide a clearer perception of the ambiguous mystical concepts and can provide an exact explanation of the mapping of an abstract concept based on a concert one. The present paper will be focused on Sohrab Sepehri, a contemporary Persian poet and painter, renowned for his composition of several acclaimed Persian modern poems and mystical tendencies. Applying the cognitive approach upon metaphysical concepts proves the Lakoffian claim, which denies the possibility of producing ‘pure’ language even in metaphysical texts. According to this theory, the relations that exist between body, brain and interaction with the environment are the builders of unconscious mind and this kind of mundane mind cannot produce pure metaphysical experiences. In the meantime, cognitive viewpoint of language changes the notion of ‘novelty’ in poetic texts and argues that poetic innovations are just ‘extending forms’ of conventional metaphors. This paper concludes that Sepehri’s mystical poems benefit from conventional cognitive metaphors about love and the complex relations between mystical metaphors are indeed the innovations that Sepehri had applied.